Internalisasi Nilai-Nilai Pendidikan Akhlak Dalam Meningkatkan Nilai Spiritual Dan Sosial Peserta Didik Di SDN Jayabakti 03 Cabangbungin - Umairoh Nurfadilah (AL-Ikhtiar : Jurnal Studi Islam, 2025)
This study aims to describe the process and success of internalizing moral education values ​​in improving the spiritual and social values ​​of students at SDN Jayabakti 03 Cabangbungin. Moral education is an important foundation in shaping students' character so that they have a balance between intellectual, spiritual, and social intelligence. In the modern era full of moral challenges, schools have a strategic role as institutions that instill moral values ​​through role models, habits, and religious activities. This study uses a qualitative approach with descriptive methods. The research subjects included the principal, teachers, and students who were selected purposively. Data were obtained through observation, interviews, and documentation, then analyzed using data reduction techniques, data presentation, and drawing conclusions. Data validity was strengthened through triangulation of sources and methods. The results of the study indicate that the internalization of moral education values ​​at SDN Jayabakti 03 Cabangbungin runs effectively through three stages, namely understanding, appreciation, and practice of moral values. Teachers play an important role as role models in instilling the values ​​of honesty, discipline, responsibility, and social concern. Religious activities such as congregational prayer, Quran recitation, and school social activities serve as a means of fostering habits that strengthen students' spiritual and social values. The success of this process is also supported by the synergy between schools and parents in continuously guiding children at home and at school.  Abstrak Penelitian ini bertujuan untuk mendeskripsikan proses dan keberhasilan internalisasi nilai-nilai pendidikan akhlak dalam meningkatkan nilai spiritual dan sosial peserta didik di SDN Jayabakti 03 Cabangbungin. Pendidikan akhlak menjadi dasar penting dalam pembentukan karakter peserta didik agar memiliki keseimbangan antara kecerdasan intelektual, spiritual, dan sosial. Dalam era modern yang sarat tantangan moral, sekolah memiliki peran strategis sebagai lembaga yang menanamkan nilai-nilai akhlak melalui keteladanan, pembiasaan, dan kegiatan keagamaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian meliputi kepala sekolah, guru, dan peserta didik yang dipilih secara purposive. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis dengan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diperkuat melalui triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa internalisasi nilai-nilai pendidikan akhlak di SDN Jayabakti 03 Cabangbungin berjalan efektif melalui tiga tahap, yaitu pemahaman, penghayatan, dan pengamalan nilai-nilai akhlak. Guru berperan penting sebagai teladan dalam menanamkan nilai-nilai kejujuran, disiplin, tanggung jawab, dan kepedulian sosial. Kegiatan keagamaan seperti salat berjamaah, tadarus Al-Qur’an, dan kegiatan sosial sekolah menjadi sarana pembiasaan yang memperkuat nilai spiritual dan sosial peserta didik. Keberhasilan proses ini juga didukung oleh sinergi antara sekolah dan orang tua dalam membimbing anak secara berkelanjutan di rumah maupun di sekolah.